Using Brazilian youtubers videos as instructional resources in Portuguese as an Additional Language: problematization and projection for didactic material production - Bambozzi Bottura, Elenora; Fanti Negri, Marcia; Buttros Gattolin, Sandra Regina (BELT - Brazilian English Language Teaching Journal, 2019)
This paper aims at presenting and discussing some potentialities and projections of the use of instructional resources for teaching Portuguese as an Additional Language (PAL) with videos of Brazilian youtubers. These kind of videos are considered as authentic materials, which bring out, through samples of real-life language in use, opportunities to develop the linguistic-communicative competence in the teaching context of PAL. Besides, they facilitate the work with different dimensions of the Portuguese language and Brazilian culture. Based on the theories of critical literacy in language teaching (Duboc, 2012; Menezes de Souza, 2011; Monte-Mór, 2012; 2013), we aim at developing learner’s linguistic-communicative competence by making use of critical-reflexive practices. This contribution is part of an ongoing project to elaborate instructional materials for teaching PAL.